A Field Test of Major Value Frameworks in Chemotherapy of Nasopharyngeal Carcinoma—To Know, Then to Measure - Zhang, Yuan; Liu, Xu; Li, Ying-Qin; Tang, Ling-Long; Chen, Lei; Ma, Jun (Frontiers in Oncology, 2020)
Background: The European Society for Medical Oncology (ESMO) and the American Society of Clinical Oncology (ASCO) have independently developed their own frameworks to assess the benefits of different cancer treatment options, which have significant implications in health science and policy. We aimed to compare these frameworks in nasopharyngeal carcinoma. Methods: We identified all randomized controlled trials of systemic therapies for nasopharyngeal carcinoma. Trials were eligible if significant differences favoring the experimental group in a prespecified primary or secondary outcome were reported. Two assessors independently scored the trials and the final scores were determined by consensus. Results: Thirteen trials were included in the analysis. Five different toxicity grading criteria were applied to the 13 trials. Nine (69.2%) trials did not report grade 1–2 toxicities and six (46.2%) did not report late toxicities. The number of acute toxicities reported was strikingly different (17 vs. 8) in two trials using the same regimen. All trials met the ESMO criteria for a high level of benefit. However, significant variations in ASCO scores between trials were observed (mean [standard deviation]: 40.0 [22.3]). Two trials with almost identical design had same ESMO grades but scored very differently for toxicity (2 vs. 18) and final scoring (76 vs. 31), using the ASCO framework. Conclusions: The underreporting and inconsistent reporting of toxicities would significantly impair the assessment of value using any framework. Moreover, there is a concern that the ASCO framework generated highly inconsistent scoring for treatments that met the ESMO criteria for a high level of benefit. The anomalies identified in the frameworks function would be helpful in their future improvement.